TEACHING MATHEMATICS AT VOCATIONAL HIGH SCHOOLS AND STUDENT ATTITUDES AND APPROACHES TOWARDS THIS COURSE - Dinç, Emre; Memnun, Dilek Sezgin; Aydın, Bünyamin (PEOPLE: International Journal of Social Sciences, 2018)
We examined the observations of preservice mathematics teachers in relation to mathematics teaching and teaching methods at vocational high schools and also their thoughts about vocational high school student attitudes and approaches towards this course in this qualitative study which is a case study of a descriptive type. With this aim, a total of 50 preservice teachers were addressed two research problems. The data reached within the context of the study was analyzed through the content analysis method. The research data were broadly analyzed by using the methods of categorical analysis and the frequency analysis. The findings showed that the preservice teachers thought that the way of teaching mathematics at vocational high schools and the vocational high school student attitudes and approaches towards this course were mostly negatively affected by such different variables as participation in courses, special teaching methods and techniques, and teacher. Besides, almost all the preservice teachers wrote negative statements in relation to the vocational high school student attitudes and approaches towards mathematics.